2009
DOI: 10.1128/aac.00862-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Screening Methods To Detect Plasmid-Mediated AmpC in Escherichia coli , Klebsiella pneumoniae , and Proteus mirabilis

Abstract: There are currently no standardized phenotypic methods for the screening and detection of AmpC enzymes. This study aimed to evaluate different methods to detect AmpC enzymes in Escherichia coli, Klebsiella spp., and Proteus spp., comparing the results from two disk-based methods and an agar dilution method. AmpC activity was determined for 255 clinical isolates by use of a three-dimensional enzyme assay combined with a multiplex PCR assay for plasmid-borne ampC genes. These results were compared against a disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
163
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(181 citation statements)
references
References 24 publications
9
163
1
8
Order By: Relevance
“…Multiplex PCR was used for bla AmpC genes [19]. Amplimers resulting from these PCR reactions were sequenced to confirm the identity and specific variant of each gene identified, and sequences were aligned to known reference sequences using ClustalW (http://www.ebi.ac.uk/Tools/clustalw2/index.html).…”
Section: Amplification Of Beta-lactam Genesmentioning
confidence: 99%
“…Multiplex PCR was used for bla AmpC genes [19]. Amplimers resulting from these PCR reactions were sequenced to confirm the identity and specific variant of each gene identified, and sequences were aligned to known reference sequences using ClustalW (http://www.ebi.ac.uk/Tools/clustalw2/index.html).…”
Section: Amplification Of Beta-lactam Genesmentioning
confidence: 99%
“…Despite this fact, coproduction of AmpC and ESBLs has been documented in many studies (Grover et al, 2013;Doi and Paterson, 2007;Bakthavatchalu et al, 2013;Mohanty et al, 2010). Prevalence of AmpC producers have been reported to be from 8% to as high as 41.3% in various studies from India and from 1.15% to as high as 46.7% in various studies from other countries (Peter-Getzlaff et al, 2011;Grover et al, 2013;Bakthavatchalu et al, 2013;Polsfuss et al, 2011;Li et al, 2003;Singhal et al, 2005;Manoharan et al, 2012;Maraskolhr et al, 2014;Rudresh and Nagarathnamma, 2011;Tan et al, 2009;Helmy and Wasfi, 2014;Ingram et al, 2011;Yilmaz et al, 2013;Coudron, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…However, Tan et al, (2009) demonstrated that using of CC-DD test accurately detected the majority of AmpC-positive isolates with best sensitivity and specificity; both (95%) when using a ≥ 4mm increase in zone diameter as a cutoff and 200µg as cloxacillin concentration on 255 clinical isolates of Enterobacteriaceae. Similarly, found that the sensitivity for CC-DD test for detection of AmpC was 97.2% and the specificity was 100% when using the same concentration and the same cutoff compared to both Modified three dimensional test and PCR.…”
Section: Cloxacillin Combined Disk Diffusion Test (Cc-dd)mentioning
confidence: 99%
“…However, they are expensive and not available in all institutions as routine tests. So, various phenotypic methods have been developed such as AmpC disk test (Mohamudha et al, 2012), modified double disk test (Singhal et al, 2005), cefoxitin-cloxacillin double-disk synergy test (CC-DDS) , modified three dimensional test (Shahid et al, 2004), cefoxtin agar medium method (Nasim et al, 2004), agar dilution method using cefoxitin with and without added cloxacillin (Tan et al, 2009) and Etest AmpC .…”
Section: Introductionmentioning
confidence: 99%